Teori Psikodinamika : Perspektif Multikultural Dalam Trend Pendekatan Psikodinamika - Annur RizqiahPutri Wijaya; Lisa Septiani; Nilam Anggieta Tirtasari (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
The psychodynamic approach includes a deep understanding of the complex interactions between culture and individual psychological aspects. This approach combines elements of psychodynamics, such as unconscious conflict and psychosexual development, with sensitivity to the role of culture in shaping a person's identity and thought patterns. The aim of this research is to understand in depth the multicultural view in the psychodynamic approach. By using literature study research methods which involve collecting, reviewing, and synthesizing information from relevant text sources to answer research questions or develop arguments. This study supports the aspect of cultural integration in psychodynamic practice to understand mental dynamics in a multicultural context. Psychodynamics in multiculturalism tends to emphasize the importance of understanding the complexity of individuals by considering their cultural background. These conclusions indicate the need to integrate multicultural aspects in psychodynamic practice to understand and respond to the diversity of human experience more holistically